2008
DOI: 10.1089/vim.2008.0025
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Levels of Circulating IL-21 in HIV-Infected AIDS Patients: Correlation with CD4+ T-Cell Counts

Abstract: IL-21 is a relatively newly discovered multifunctional and pleiotropic cytokine. It is produced primarily by CD4(+) T cells, the principal targets of the virus, and therefore this cytokine has special relevance to HIV infection. Here we show for the first time that serum levels of this cytokine are significantly reduced in HIV-infected AIDS patients and correlate significantly with their CD4(+) T-cell counts. These data suggest that the cytokine levels could act as a valuable biomarker for the progression of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 15 publications
3
53
0
1
Order By: Relevance
“…Recent experiments with mice have established that interleukin-21 (IL-21) is the major mediator produced by CD4 T cells that promotes optimal CD8 T cell functions during chronic viral infection (84,101,272). Circulating IL-21 concentrations are reduced in HIV-infected subjects and correlate with CD4 T cell counts (130,131), indicating that CD4 T cells are an important source of IL-21 in humans as well as in mice. Taken together, there is evidence that HIV infection can indirectly lead to the depletion of CD8 T cells that recognize microbial antigens, and this may contribute to susceptibility to opportunistic infections, including TB.…”
Section: Hiv Effects On Tb Immunity: Evidence For and Against Selectimentioning
confidence: 99%
“…Recent experiments with mice have established that interleukin-21 (IL-21) is the major mediator produced by CD4 T cells that promotes optimal CD8 T cell functions during chronic viral infection (84,101,272). Circulating IL-21 concentrations are reduced in HIV-infected subjects and correlate with CD4 T cell counts (130,131), indicating that CD4 T cells are an important source of IL-21 in humans as well as in mice. Taken together, there is evidence that HIV infection can indirectly lead to the depletion of CD8 T cells that recognize microbial antigens, and this may contribute to susceptibility to opportunistic infections, including TB.…”
Section: Hiv Effects On Tb Immunity: Evidence For and Against Selectimentioning
confidence: 99%
“…Indeed, on the basis of results from a small cross-sectional study, we reported earlier that serum levels of the cytokine were significantly reduced in patients with chronic HIV infection (26). We have now performed much larger cross-sectional and longitudinal studies to better understand the dynamics of cytokine production in different stages of the infection.…”
mentioning
confidence: 99%
“…Nos études ont permis de montrer que les taux sériques d' IL-21 étaient considérablement réduits chez les patients infectés par le VIH-1 [22,23]. Ces études ont été réalisées dans une large cohorte de patients au stade de la primo-infection, chez des patients chroniquement infectés avec ou sans traitement antirétroviral ainsi que chez différentes catégories de patients non progresseurs à long terme (aussi appelés « contrôleurs élites ») [38].…”
Section: Rôle De L'il-21 Dans Le Contrôle De L'infection Par Le Vih-1unclassified